Use of Expanded Polystyrene (EPS) and Shredded Waste Polystyrene (SWAP) Beads for Control of Mosquitoes - A Soltani; H Vatandoost; H Jabbari; AR Mesdaghinia; AH Mahvi; M Younesian; AA Hanafi-Bojd; S Bozorgzadeh; MR Abai; A Pakari; H Shabkhiz (Tehran University of Medical Sciences, 2008)
Background: Mosquitoes transmit several diseases to human. There are several measures for control of larvae. As part of Integrated Vector Management (IVM) program, the utility of floating layers of polystyrene beads (EPS) is a potential alternative in habitats of mosquito larva. EPS beads prevent oviposition of mosquito as well as killing the immature stages by forming a tick layer on the water surface.  They are cheap, environmentally safe and do not need frequent application and remain on the surface of water for long time. The objective of the current study was to asses the effectiveness of two types of polystyrene beads of (EPS) and (SWAP) for control of mosquito larvae under laboratory conditions. Methods: Anopheles stephensi and Culex quinquefasciatus were used for experimental purposes. In each tray 250 larvae of late 3rd and early 4th instars were introduced. The experiment was conducted on 4 replicates for An. stephensi, Cu. quinquefasciatus and combination of both. Emerging of adult mosquitoes were calculated every day until the end of experiments. Results: Mortality rate and Inhibition of Emerge (IE) for Cu. quinquefasciatus, An. stephensi and combination of both species was 97.8%, 100% and 99.07%, respectively using EPS. In average, EPS was able to kill 98.9% of larvae. The figures with SWAP were 63%, 91.05% and 72.65%, respectively. The average mortality for mosquitoes was 75.57% Conclusion: EPS and SWAP beads can be very effective and practical for elimination of An. stephensi and Cx. quinquefasciatus under the laboratory conditions.